Mapping Phyllosilicates on the Asteroid Bennu Using Thermal Emission Spectra and Machine Learning Model Applications. Issue 20 (20th October 2022) - Breitenfeld, L. B.; Rogers, A. D.; Glotch, T. D.; Kaplan, H. H.; Hamilton, V. E.; Christensen, P. R.
Abstract: Bennu, the target of the OSIRIS‐REx mission, is an asteroid with compositions analogous to low petrologic type CI, CM, CR, and/or ungrouped carbonaceous chondrites. Asteroids like Bennu provide information about the building blocks of the early Solar System. Analysis of the mid‐infrared remote sensing data informs mineral quantification. We apply a phyllosilicate specific model, developed by Breitenfeld et al. (2021, https://doi.org/10.1029/2021je007035 ) that distinguishes between Mg and Fe serpentines, to Baseball Diamond 1 (BBD1), equatorial station 3 (EQ3), and touch‐and‐go OSIRIS‐REx thermal emission spectrometer data. The average total phyllosilicate predictions are 73 (BBD1) and 72 vol% (EQ3). We observe higher Fe‐cronstedtite and lower Mg‐rich serpentine content in the equatorial region of Bennu than average. Mid‐infrared spectral variability may be explained by sorting effects through mass movement. Plain Language Summary: Bennu is an asteroid made of primitive materials that provide information about the early Solar System. Using infrared emission spectra and machine learning modeling, we estimate the amount and composition of phyllosilicate minerals across the surface of Bennu. Our results suggest that Bennu is primarily composed of phyllosilicate minerals as expected from previous studies. Mg‐ and Fe‐rich serpentine abundances are mapped across the asteroid Bennu. Near the equator, our model predicts higher cronstedtite (Fe‐rich serpentine) and lower Mg‐rich serpentine compared to the average composition of the asteroid. The spectral and compositional variability on Bennu can be explained by aqueous processing and sorting effects. Key Points: We estimate Bennu's phyllosilicate content is primarily Mg‐rich serpentine with smaller amounts of cronstedtite and saponite We predict higher cronstedtite and lower Mg‐rich serpentine abundances in the equatorial region and vice versa for the middle latitudes We observe thermal emission spectrometer spectral variability between the equatorial and middle latitude regions of Bennu that may be due to sorting effects